Precision medicine-guided co-delivery of ASPN siRNA and oxaliplatin by nanoparticles to overcome chemoresistance of colorectal cancer. (November 2022) - Huang, Cheng-Zhi; Zhou, Yue; Tong, Qi-Song; Duan, Qi-Jia; Zhang, Qing; Du, Jin-Zhi; Yao, Xue-Qing
Abstract: The development of chemoresistance is a major hurdle for the treatment of colorectal cancer (CRC), which contributes remarkably to the poor clinical prognosis. Nanodrug delivery systems show great potential in overcoming chemoresistance, but limited by the lack of identification of chemoresistance targets from cancer patients. In the present study, we enrolled chemotherapy-resistant or sensitive CRC patients and used the next-generation RNA sequencing to reveal that Asporin (ASPN) is highly expressed in tumor tissues from oxaliplatin (OXA)-resistant patients and closely correlated with a poor prognosis of CRC. Downregulation of ASPN reversed OXA resistance and promoted cell apoptosis both in vitro and in vivo . To overcome ASPN-mediated OXA resistance, we constructed a nanoparticle-based co-delivery system (denoted as PPO-siASPN) for simultaneous delivery of OXA and siRNA targeting ASPN (siASPN). PPO-siASPN not only facilitated the intracellular delivery of OXA through the enhanced cellular uptake, but effectively suppressed ASPN expression for synergistic antitumor activity in vitro and in vivo . In the more clinically relevant patient-derived xenograft (PDX) mouse model, systemic administration of PPO-siASPN achieved a remarkable therapeutic effect. This study uncovered the critical role of ASPN in causing OXA resistance in CRC patients and suggests a promising nanoformulation that may be more effective than current standard-of-care medications.